Effect of Optical Eccentricity of Human Eye on Vision Quality - Al-Awsi, Suha Mousa Khorsheed (Al-Nahrain Journal of Science, 2012)
The purpose of this paper is to give detailed explanations to the eccentricity related errors of human eye. An optical metrology is studied to determine the errors present in the eccentric eye with respect to emmtropic eye. To study optical metrology, the forms of errors that might be present need to be analyzed in the eye design. The possible eccentric errors were considered and produced on the adopted eye optical design. The most interesting optical functions were estimated and evaluated, the results showed a significant effect impacts the optical functions due to the eccentricity. The degradation of vision quality was interpreted according to the behavioral comparison between the estimated functions of the eccentric eye with respect to emmtropic eye. This study offers the chance for the researchers in the eye related topics to dissolve the vagueness concerning with the complexity of human eye design, and introduce a qualitative and quantitative analyses to consider the subject of human eye design and activities.